Acting Optimally for Biodiversity in a World Obsessed with REDD+. Issue 6 (12th April 2013) - Venter, Oscar; Hovani, Lex; Bode, Michael; Possingham, Hugh
Abstract REDD+ presents novel options for conservation in the tropics, yet it is unclear how biodiversity‐focused organizations or actors should react to these carbon‐focused opportunities. Here, we critically assess for the first time the expected outcomes of five contrasting scenarios of engagement between a biodiversity actor and REDD+. We discover that in the Berau regency, Indonesia, it is usually beneficial for a biodiversity actor to react in some way to REDD+, but the preferred reaction depends on whether a REDD+ project is already developing in the region, and the scale and type of conservation objectives. In general, from a strict biodiversity perspective, the most cost efficient reaction to the presence of REDD+ is to use biodiversity funds to protect areas neglected by REDD+. Our results demonstrate that if biodiversity actors fail to adapt the way they pursue conservation in the tropics, REDD+ opportunities could go largely untapped.